2016
DOI: 10.22161/ijeab/2.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of agricultural soils in the area of Jorf Lasfar (El Jadida-Morocco)

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Sampling was performed from six sites located in the north and central of Tunisia, namely, Manzel bouzalfa (MB), Bni Khaled (BK), El kef (EK), Bizerte (BZ), Beja (BJ) and Sidi bouzid (SB) which were classified as sandy soil, excepting EK site which was sandy-clay (Fig. 1A, Supplementary Table 1) according to Moustarhfer et al (2017). From each site three representative C. sinensis trees were selected.…”
Section: Studied Sites and Soil Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampling was performed from six sites located in the north and central of Tunisia, namely, Manzel bouzalfa (MB), Bni Khaled (BK), El kef (EK), Bizerte (BZ), Beja (BJ) and Sidi bouzid (SB) which were classified as sandy soil, excepting EK site which was sandy-clay (Fig. 1A, Supplementary Table 1) according to Moustarhfer et al (2017). From each site three representative C. sinensis trees were selected.…”
Section: Studied Sites and Soil Samplingmentioning
confidence: 99%
“…Tunisia. An aliquot of the collected samples was dried at room temperature and subjected to the following physicochemical analyses as previously described by Moustarhfer et al (2017): organic matter (OM), pH, carbon (C), inorganic carbon (CaCO 3 ), potassium (K), nitrogen (N), phosphorus (P), assimilable phosphorus (P 2 O 5 ) and exchangeable potassium (K 2 O). Salinity was analyzed by measuring electrical conductivity (EC) (Supplementary Table 1).…”
Section: Physico-chemical Analysismentioning
confidence: 99%
“…The results of the physico-chemical analysis of the water from the Doukkala water table showed that the conductivity, sodium and chlorides generally testify that the quality of water from poor quality wells according to Moroccan standards (CNS, 1994) except for P2 and P8. Thus, the nitrate concentration in all the wells show values less than or equal to the standards for drinking water 50 mg/L according to the World Health Organization (WHO) except for the well P1, P3, P4, P5 which exceeds the standards, this confirms the impact of the intensification of agriculture and may be the discharge of domestic and industrial wastewater (Moustarhfer, K. 2016;Boualla,O. (2016) ; Hamdani, A (2001).…”
Section: Discussionmentioning
confidence: 64%